Ciências sociais na América Latina: privilégio epistemológico, estilo original - Campos Motta, Renata (Revista debates, 2009)
This essay explores how Latin America offers a privileged locus for the social scientist to cope with the epistemological challenge of adjusting theory and empiria. The argument is that although this is a challenge common to all social scientists, it becomes more explicit as such for the social scientist in the region, as he/she exercises a profession from which the theoretical and conceptual formulations were developed in a tradition from another time and place. In adjusting theories, concepts and the Latin American contemporary reality, he or she expands, in an original way, the universality of the Social Sciences disciplinary matrix.
Gesehen am 26.04.2023